Broad Spectrum Antioxidant Properties of 20 Indian Medicinal Plants. Issue 2 (2nd April 2016) - Zahin, Maryam; Ahmad, Iqbal; Shireen, Iram; Husain, Fohad Mabood; Aqil, Farrukh
ABSTRACT: Antioxidant properties of methanol extracts of 20 plants were studied by four different assays over a range of concentrations (12.5–400 µg mL −1 ), and compared with standard antioxidants' ascorbic acid and butylated hydroxytoluene. Ascorbic acid–equivalent antioxidant activity of extracts by the phosphomolybdenum method ranged from 392.8 to 2942.7 µmoles g −1 at 400 µg mL −1, whereas DPPH radical scavenging was between 30.9% and 95.2%; extracts also showed strong activity by FRAP and CUPRAC assays. The extracts demonstrated dose-dependent activity and strong correlation between antioxidant activities and total phenolics. Total phenolic content was the highest in Syzygium aromaticum (279 mg GAE g −1 ) and the lowest in Sesame indicum (28.16 mg GAE g −1 ).